Systematic review protocol: an assessment of the post-approval challenges of autologous CAR-T therapy delivery. Issue 7 (4th July 2019) - Lam, Ching; Meinert, Edward; Halioua-Haubold, Celine-Lea; Carter, Alison; Yang, Aidong; Brindley, David; Cui, Zhanfeng
Abstract : Introduction: Following recent regulatory approvals of two chimeric antigen receptor T-cell (CAR-T) therapies, the field now faces a number of post-approval challenges. These challenges are in some respects defined and, in others, uncertain due to the nascence of the field. At present, information pertaining to such post-approval challenges are scattered in various previous reviews or raised in singular papers reporting experience in working with the therapy. This systematic review is designed to evaluate and summarise the post-approval challenges for robust delivery of CAR-T therapies to inform future work on the optimisation of CAR-T delivery to patients. Methods and analysis: We will search Medline, EMBASE (OvidSP), BIOSIS & Web of Science, Cochrane Library, ICER database, NICE Evidence Search, CEA Registry, WHOLIS WHO Library and Scopus for studies published between 2014 and the present. In addition, a Google search for grey literature such as bioprocess blog posts, opinion pieces, press releases and listed companies involved in CAR-T development annual reports will be conducted. Two authors will independently screen the titles and abstracts identified from the search and accept or reject the studies according to the study inclusion criteria and any discrepancies will be discussed and resolved. The quality of the selected literature will be assessed using the Critical Appraisal Skills Programme (CASP) Systematic Review checklist and grey literature will be assessed using the Authority, Accuracy, Coverage, Objectivity, Date, Significance (AACODS) checklist. Data from eligible publications will be categorised using a flowchart and extracted using a data abstraction form. Qualitative and quantitative analysis of the post-approval challenges of CAR-T therapies will be conducted based on the results attained. Ethics and dissemination: The executed study will be published in a peer-reviewed journal in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The findings from this review will be used to inform the development of an optimisation model for robust delivery of CAR-T therapies using a systems engineering approach. Trial registration number: CRD42018109756.